A Comprehensive Practice Guide for Debussy’s Sonata for Cello and Piano - Buga-ay, Andreia Claudette G.; Trakulhun, Wiboon (Rangsit Music Journal, 2025)
Claude Debussy was one of the most prominent and influential figures in classical music towards the end of the Romantic period and the early Twentieth century. Generally known for his compositions for piano and orchestra, his chamber music works have often been overlooked. Composed in 1915, Debussy’s Sonata for Cello and Piano marked Debussy’s return to composition after a period of inactivity. The Sonata for Cello and Piano reflects compositional techniques from the 17th and 18th centuries while showcasing his refined and innovative techniques over the span of his career. The Sonata for Cello and Piano departs from traditional forms of the Classical and Romantic periods, incorporating Impressionistic elements such as fluid tonalities, ambiguous harmonies, and unpredictable rhythms, which challenge performers to experiment with their technical and interpretative skills. Comprised of three movements—Prologue, Sérénade, and Finale—the Sonata for Cello and Piano demonstrates Debussy’s ingenuity and expressive depth. This research examines the technical challenges in Sonata for Cello and Piano and offers methods to address them, while incorporating the researcher’s interpretative insights. It focuses on bowings, fingerings, special effects, dynamics, expression, tempo, and ensemble, supported by a detailed practice guide. A Comprehensive Practice Guide for Debussy’s Sonata for Cello and Piano is based on artistic research. Music performance’s structured daily routines make it well-suited to practice-based methods, allowing for systematic recording and analysis of techniques and interpretative approaches. The initiation of the research was first established with the selection of the piece. The researcher will then review a variety of literature including relevant books, articles from peer-reviewed journals, theses and dissertations collected from ProQuest, audio recordings, and videos of masterclasses in order to build a strong foundation for studying Debussy’s Sonata for Cello and Piano. Data collected in the preliminary phase do not hold conclusive results. Therefore, substantial findings will be derived from the process of artistic research drawn from the researchers own experience during the preparation for the performance of the sonata. The researcher will be actively involved in the creative process of experimenting with techniques and interpretation during practice. Simultaneously, the researcher will reflect on the results of the creative process and document them in detail. Being that artistic research is an iterative process, this will require the researcher to revisit and refine their own work. By embracing this approach, not only will this foster continuous improvement but also enable a more profound exploration of the artistic possibilities. The practice guide is laid out mainly into two parts. The first part presents the researcher’s interpretation of the Sonata for Cello and Piano whereas the second part presents efficient solutions and methods of practice for addressing technical challenges inherent in the sonata. A recurring challenge in the Sonata for Cello and Piano is phrasing. Although Debussy’s original slurs are intended to shape the phrasing, they can create technical difficulties during performance. To overcome these challenges, the researcher presents modified bowings and fingerings that maintain Debussy’s artistic intentions. The Sonata for Cello and Piano highlights timbre and presents interpretative challenges. Pizzicato plays a significant role in the Sonata for Cello and Piano, featuring six types of pizzicati—pizzicato with staccato, pizzicato with tenuto, chord pizzicato, slurred pizzicato, pizzicato marked with arraché, and left-hand pizzicato. For each type of pizzicato, the researcher has designed specific methods of execution. Furthermore, the researcher has assigned specific techniques such as spiccato, sautillé, and ricochet to certain passages in order to effectively perform each passage. Both artificial and natural harmonics appear in the sonata, however, the researcher presents more than one way in which these can be played. The practice guide enhances the interpretative analysis by providing practical solutions to the technical challenges in the sonata. It underscores the importance of precise bowing techniques and systematic fingerings, particularly in passages featuring frequent string crossings, contrasting dynamics, rapid runs, and wide leaping intervals. This research offers a simple corrective string crossing exercise, methods to achieve seamless string crossing, points on how to use specific bow techniques for certain passages, and four practice methods for the left hand. This research provides a comprehensive analysis of Debussy’s Sonata for Cello and Piano, offering performers practical guidelines to improve technical skills and interpretative understanding. By emphasizing the connection between technique and expression, it highlights that successful interpretation requires both technical mastery and emotional depth. The research combines scholarly insight with practical guidance, equipping cellists to approach the sonata meaningfully and bring their unique voice to the music. While focused on Debussy’s work, the methods presented serve as a flexible framework applicable to other musical genres and repertoires, encouraging musicians to adapt these methods across styles and periods.